2022
DOI: 10.46328/ijemst.2842
|View full text |Cite
|
Sign up to set email alerts
|

Digital Competencies: Are Pre-Service Teachers Qualified for Digital Education?

Abstract: This study examines digital competency (DigComp) as a crucial component of twenty-first century teachers. It investigates pre-service teachers’ level of DigComp from their perspective, and whether they felt their preparation programme qualified them for digital education. One hundred forty student teachers in their final year of majoring in either art education or kindergarten at a public university in Saudi Arabia participated. Data was collected via an online survey that included five DigComp areas: informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Skills in creating interesting digital content need to be studied further, especially for prospective teacher students so that they can convey meaningful learning content messages for students. Pre-service teacher education programs need to make adjustments and evaluations in equipping students with cognitive, teaching, and digital skills needed in education in the technological era (Alnasib, 2023). Digital content creation can be utilized in creating a learning environment that is interactive, interesting and relevant to student learning needs.…”
Section: Resultsmentioning
confidence: 99%
“…Skills in creating interesting digital content need to be studied further, especially for prospective teacher students so that they can convey meaningful learning content messages for students. Pre-service teacher education programs need to make adjustments and evaluations in equipping students with cognitive, teaching, and digital skills needed in education in the technological era (Alnasib, 2023). Digital content creation can be utilized in creating a learning environment that is interactive, interesting and relevant to student learning needs.…”
Section: Resultsmentioning
confidence: 99%
“…The utilization of digital tools to provide instruction to pre-service technical and vocational students holds immense significance and urgency within the contemporary era [22]. In the aftermath of the transformative impact of the COVID-19 pandemic on educational paradigms, the mastery of digital competencies has emerged as a pivotal skill set for aspiring educators in this new epoch [23]. This is underscored by the escalating demand for communication tools in the educational landscape, necessitating both students and technical and vocational educators to adeptly employ a plethora of tools to interact with learners and pedagogical overseers.…”
Section: Digital Technology For Supervision Of Teachingmentioning
confidence: 99%
“…A scholar (Lianhong, 2022) describes the global transition to distance education accelerated by the COVID-19 pandemic, accompanied by challenges for digital infrastructure. An analysis (Alnasib, 2023) showed that distance learning can provide high flexibility and accessibility but requires direct investment in technical infrastructure and teacher training. Research (Roick, 2023) indicates the importance of developing a new methodology for evaluating and verifying knowledge of online learning, as the communication of the new educational space is significantly differentiated from the traditional one.…”
Section: Literature Reviewmentioning
confidence: 99%